Comparison of P2Y12 inhibitors for mortality and stent thrombosis in patients with acute coronary syndromes: Single center study of 10 793 consecutive 'real-world' patients. (17th November 2017) - Gosling, Rebecca; Yazdani, Momina; Parviz, Yasir; Hall, Ian R; Grech, Ever D.; Gunn, Julian P; Storey, Robert F.; Iqbal, Javaid
Abstract: Three oral platelet P2Y12 inhibitors, clopidogrel, prasugrel, and ticagrelor, are available for reducing the risk of cardiovascular death and stent thrombosis in patients with acute coronary syndromes (ACS). We sought to compare the efficacy of these antiplatelet drugs in contemporary practice. Data were collected for 10 793 consecutive ACS patients undergoing coronary angiography at Sheffield, UK (2009–2015). Since prasugrel use was mostly restricted to the STEMI subgroup, clopidogrel and ticagrelor were compared for all ACS patients, and all three agents were compared in the STEMI subgroup. Differences in outcomes were evaluated at 12 months by KM curves and log-rank test after adjustment for independent risk factors. Of 10 793 patients with ACS (36% STEMI), 43% (4653) received clopidogrel, 11% (1223) prasugrel and 46% (4917) ticagrelor, with aspirin for all. In the overall group, ticagrelor was associated with lower all-cause mortality compared with clopidogrel (adjusted hazard ratio (adjHR) 0.82, 95% confidence intervals (CI) 0.71–0.96, p = 0.01). In the STEMI subgroup, both prasugrel and ticagrelor were associated with a lower mortality compared with clopidogrel (prasugrel vs. clopidogrel: adjHR 0.65, CI 0.48–0.89, p = 0.007; ticagrelor vs. clopidogrel: adjHR 0.70, CI 0.61–0.99, p = 0.05). Of the 7595 patients who underwent PCI, 78 (1.0%) had definite stent thrombosis by 12 months. Patients treated with ticagrelor had a lower incidence of definite stent thrombosis compared with clopidogrel (0.6% vs. 1.1%; adjHR 0.51, CI 0.29–0.89, p = 0.03). In the STEMI subgroup, there was no significant difference between the three groups (ticagrelor 1.0%, clopidogrel = 1.5%, prasugrel = 1.6%; p = 0.29). In conclusion, ticagrelor was superior to clopidogrel for reduction in both mortality and stent thrombosis in unselected invasively managed ACS patients. In STEMI patients, both ticagrelor and prasugrel were associated with lower mortality compared with clopidogrel, but there was no significant difference in the incidence of stent thrombosis.